Deploying augmented reality to help engage the public with palaeontological applications. Issue 1 (February 2022) - Bennett, Matthew R.; Budka, Marcin; Belvedere, Matteo; Reynolds, Sally
Abstract: Augmented reality (AR) has huge potential as a science outreach tool, especially around palaeontology where it is possible to bring extinct animals to life. This paper shares our experiences as academic geoscientists in developing a series of AR applications during a three-year period. We do not focus on the technical issues of app design and coding but on the lessons learnt during this time which may be of value to others, whether academics, event coordinators or museum curators interested in using digital technology to enhance user experience or convey educational messages. We identify eight issues that are worth keeping in mind when commissioning, developing, and deploying AR apps for use as a science communication tool. The issues are: (1) download barriers; (2) ageing novelty of AR; (3) the 'stickiness' of an app tends to be moment-locations specific; (4) maintenance of bespoke apps; (5) 'boom and lapse' cycles in funding; (6) difficulty of embedding educational content; (7) priority conflict between users and event organisers; and (8) the quality of the animation is key.